Agricultural Soil Management Practices Differentially Shape the Bacterial and Fungal Microbiomes of Sorghum bicolor - Wipf, Heidi M.-L. (Appl Environ Microbiol, 2021)
Soils play important roles in biological productivity. While past work suggests that microbes affect soil health and respond to agricultural practices, it is not well known how soil management shapes crop host microbiomes. To elucidate the impact of management on microbial composition and function in the sorghum microbiome, we performed 16S rRNA gene and ITS2 amplicon sequencing and metatranscriptomics on soil and root samples collected from a site in California’s San Joaquin Valley that is under long-term cultivation with (i) standard (ST) or no tilling (NT) and (ii) cover cropping (CC) or leaving the field fallow (NO). Our results revealed that microbial diversity, composition, and function change across tillage and cover type, with a heightened response in fungal versus bacterial communities. Surprisingly, ST harbored greater microbial alpha diversity than NT, indicating that tillage may open niche spaces for broad colonization. Across management regimes, we observed class-level taxonomic level shifts. In addition, we found significant functional restructuring across treatments, including enrichment for microbial lipid and carbohydrate transport and metabolism and cell motility with NT. Differences in carbon cycling were also observed, with increased prevalence of glycosyltransferase and glycoside hydrolase carbohydrate active enzyme families with CC. Lastly, treatment significantly influenced arbuscular mycorrhizal fungi, which had the greatest prevalence and activity under ST, suggesting that soil practices mediate known beneficial plant-microbe relationships. Collectively, our results demonstrate how agronomic practices impact critical interactions within the plant microbiome and inform future efforts to configure trait-associated microbiomes in crops. IMPORTANCE While numerous studies show that farming practices can influence the soil microbiome, there are often conflicting results on how microbial diversity and activity respond to treatment. In addition, very little has been published on how the corresponding crop plant microbiome is impacted. With bacteria and fungi known to critically affect soil health and plant growth, we concurrently compared how the practices of no and standard tillage, in combination with either cover cropping or fallow fields, shape soil, and plant-associated microbiomes between the two classifications. In determining not only the response to treatment in microbial diversity and composition, but for activity as well, we demonstrate here the significance of agronomic practice in modulating plant-microbe interactions, as well as encourage future work on the mechanisms involved in community assemblages supporting similar crop outcomes.